Predictors of Dental Caries Development in 1.5-Year-Old High-Risk Children in the Japanese Public Health Service - Shihoko Sakuma, DDS, PhD; Muneto Nakamura, DDS; Hideo Miyazaki, DDS, PhD (Blackwell Synergy, 2007)
The purpose of this study was to construct prediction models for 1.5-year-old children who were at risk for the development of caries.